VALIDATION ESTIMATION OF BAICALIN DETERMINATION USING PLANAR CHROMATOGRAPHY - V. E. Kim; T. D. Mezenova; D. A. Konovalov (Фармация и фармакология (Пятигорск), 2015)
The search for available and at the effective method of quantitative determination of Baicalin in liquid complex phyto-extraction was the purpose of this work. The article shows experimental data of quantitative determination of Baicalin, received with densitometry. The method was validated, therefore there is an opportunity of its use for identification and quantitative determination of Baicalin in plants active parts.